Outcomes of an inpatient refeeding protocol in youth with anorexia nervosa: Rady Children's Hospital San Diego/University of California, San Diego. Issue 1 (December 2017) - Maginot, Tamara; Kumar, Maya; Shiels, Jacqueline; Kaye, Walter; Rhee, Kyung
Abstract Background Current guidelines for nutritional rehabilitation in hospitalized restrictive eating disorder patients recommend a cautious approach to refeeding. Several studies suggest that higher calorie diets may be safe and effective, but have traditionally excluded severely malnourished patients. The goal of this study was to evaluate the safety of a higher calorie nutritional rehabilitation protocol (NRP) in a broad sample of inpatients with restrictive eating disorders, including those who were severely malnourished. Methods A retrospective chart review was conducted among eating disorder inpatients between January 2015 and March 2016. Patients were started on a lower calorie diet (≤1500 kcals/day) or higher calorie diet (≥1500 kcals/day). Calorie prescription on admission was based on physician clinical judgement. The sample included patients aged 8–20 years with any DSM-5 restrictive eating disorder. Those who were severely malnourished (<75% expected body weight [EBW]) or required tube feeding during admission were included. Multivariable regression models were used to determine whether level of nutritional rehabilitation was associated with hypophosphatemia, hypomagnesemia, or hypokalemia. Results The sample included 87 patients; mean age was 14.4 years (S.D. 32.7); 29% were <75% EBW. The majority (75.8%) was started on higher calorie diets (mean 1781 kcal/day). Controlling for rate of calorie change, initial %EBW, age, race/ethnicity, insurance, diagnosis, and NG/NJ tube placement, higher calorie diets were not associated with hypophosphatemia, hypomagnesemia, or hypokalemia on admission or within the first 72 h. Increased risk of hypophosphatemia on admission was associated with lower baseline %EBW. Conclusion A higher calorie NRP was tolerated in this broad population of inpatients with restrictive eating disorders. Lower %EBW on admission was a more important predictor of hypophosphatemia than initial calorie level. Larger studies are required to demonstrate the safety of higher calorie diets in severely malnourished patients.